AI-Based HOTS Questions: Training for Elementary School Teachers in the Digital Era - Muhammad Rijal Fadli; Khusnul Fatonah; Imam Santosa (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The development of the digital era requires teachers to not only master conventional pedagogy, but also have the capability to manage and utilize Artificial Intelligence (AI) as part of learning and assessment innovation. However, some elementary school teachers have not fully followed these technological developments, so the preparation of Higher Order Thinking Skills (HOTS) questions tends to be done conventionally and has not optimized AI as a professional tool. This Community Service activity aims to provide training in creating AI-based HOTS questions for elementary school teachers to improve their pedagogical competence and digital literacy. The method used is Participatory Action Research (PAR), with stages of socialization, training, technology implementation, mentoring, and program sustainability by emphasizing the active participation of partners. The activity was carried out through collaboration between the proposing team and the target community, namely teachers of Setia Mulya 02 Bekasi Elementary School, so that the materials and practices provided are aligned with the school's needs. The results of the program implementation showed a significant increase in teacher understanding and skills, with more than 70% of participants being able to independently prepare AI-based HOTS questions. These findings confirm that the Community Service Program is relevant to the demands of learning in the digital era and significantly contributes to improving the quality of assessments that are contextual, technology-adaptive, and oriented toward developing students' higher-order thinking.